Khidmatu Firanda Andirja li Tanmiyati Fahmi Al-Muslimīna bi Al-Tafsīr Aṣ-Ṣahīh li Al-Qur’ān Al-Karīm fī Indunisiyā: خدمة فيراندا أنديرجا لتنمية فهم المسلمين بالتفسير الصحيح للقرآن الكريم في إندونيسيا - Ramadhan, Abdul Rahman; Nugroho, Kevin Zidane; Zainal, Muhammad; El Farabi, Muhammad Nadzif; Zain , Bayu Rizky Fachri (ZAD Al-Mufassirin, 2023)
The research aims to analyze the contribution of Dr. Firanda Andirja in the development of the science of Quranic exegesis in Indonesia, especially in building a correct understanding of Quranic exegesis among the Muslim community. Dr. Firanda Andirja is one of the scholars who actively contribute to the development of Quranic exegesis in Indonesia through his contributions in building the Muslim community’s understanding of authentic Quranic exegesis through his lectures, writings, and utilization of digital platforms. This research is qualitative research. The data collection method used in this research is literature review. The results of this research show that Firanda's contribution in building a correct understanding of tafsir in Indonesia is by conducting lectures in Indonesian on Qur'anic tafsir, writing books on Qur'anic tafsir in Indonesian, and learning tafsir through digital platforms.